2017
DOI: 10.1186/s12890-016-0346-6
|View full text |Cite
|
Sign up to set email alerts
|

What patients really think about asthma guidelines: barriers to guideline implementation from the patients’ perspective

Abstract: BackgroundTreatment of asthma does not always comply with asthma guidelines (AG). This may be rooted in direct or indirect resistance on the doctors’ and/or patients’ side or be caused by the healthcare system. To assess whether patients’ concepts and attitudes are really an implementation barrier for AG, we analysed the patients’ perspective of a “good asthma therapy” and contrasted their wishes with current recommendations.MethodsUsing a qualitative exploratory design, topic centred focus group (FG) discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 33 publications
(44 reference statements)
4
60
1
1
Order By: Relevance
“…More specifically, patients were satisfied with counselling that discussed asthma and its features, medication, and how to manage symptoms; this agrees with research by Lee et al (2016), who reported that counselling improves patients' knowledge of the disease and inhalation technique. Lingner et al (2017) reported contrasting findings, namely that patients were unsatisfied with counselling time and felt that they were not treated as an expert in their own asthma disease. Therefore, patients should always be afforded ample time to discuss their problems and be motivated to care for themselves.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More specifically, patients were satisfied with counselling that discussed asthma and its features, medication, and how to manage symptoms; this agrees with research by Lee et al (2016), who reported that counselling improves patients' knowledge of the disease and inhalation technique. Lingner et al (2017) reported contrasting findings, namely that patients were unsatisfied with counselling time and felt that they were not treated as an expert in their own asthma disease. Therefore, patients should always be afforded ample time to discuss their problems and be motivated to care for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, successful counselling requires active interaction between the patient and healthcare staff. Only a few studies have investigated counselling from the viewpoint of an asthma patient (Lingner et al 2017), with most of the previous research focusing on counselling interventions (e.g., Clark et al 2010) or self-care (e.g., Gibson et al 2009). This study examines adult asthma patients' perceptions of counselling quality, with the quality of counselling described based on the content, implementation, and benefits of counselling, along with the available resources for counselling.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations